Fresh, grown, made, and proud: How state governments use stewardship to collectively promote their state’s food products - Laura Witzling (Journal of Applied Communications, 2021)
Many U.S. state governments have programs that promote the food grown or made within their state. In this study, the websites of 41 such programs were analyzed for indicators of stewardship, a framework concerned with relationship cultivation. Several of the indicators were observed commonly, demonstrating a generally balanced use of stewardship strategies by the programs. The websites also provided a platform to grow relationships between producers and consumers. One recommendation for managers of statewide food promotion programs, or similar umbrella food brand programs, is to examine their own websites to ensure indicators of all stewardship strategies are present. Though most websites examined in this study posted mission statements, for example, not all of them did. Expressions of gratitude to multiple stakeholder groups were also lacking on many of the websites. Another recommendation for managers is to implement some of the more creative ways programs have practiced stewardship such as giving audiences opportunities to co-create content. Overall, this analysis showed that state-run food promotion programs function as public relations and agricultural communications tools.
Keywords: agricultural communication; government public relations; local food; stewardship